Iron-carbon membrane filtering material as well as preparation method and application thereof
By using components such as sponge iron powder and activated carbon powder, the iron-carbon film filter material prepared and modified, the problem of poor porosity of existing materials is solved, and the sewage treatment effect is significantly improved.
Patent Information
- Application Number
- CN202411807408.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-04-11
AI Technical Summary
The porosity of existing iron-carbon film filter materials is poor, which affects the sewage treatment effect.
Iron carbon film filter material is prepared by pressing and sintering processes and modified by polytetrafluoroethylene solution to improve its porosity and adsorption properties.
The porosity and adsorption performance of iron-carbon film filter materials are significantly improved, the treatment effect on sewage is enhanced, and the COD value of organic pollutants and suspended matter in sewage is reduced.
Smart Images

Figure CN119793071A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of filter materials, and in particular to an iron-carbon membrane filter material and a preparation method and application thereof. Background Art
[0002] Iron-carbon membrane is a thin film material composed of iron and carbon. It is widely used in sewage treatment because of its high porosity and can effectively remove organic pollutants and suspended solids in sewage. However, the current iron-carbon membrane filter material usually has a poor porosity, which affects the sewage treatment effect. Summary of the invention
[0003] The main purpose of the invention is to provide an iron-carbon membrane filter material and a preparation method and application thereof, aiming to improve the treatment effect of the iron-carbon membrane filter material on sewage.
[0004] To achieve the above object, the present invention provides an iron-carbon membrane filter material, comprising the following components: sponge iron powder, activated carbon powder, sodium silicate, calcium chloride, hydroxypropyl cellulose, expanded perlite and a catalyst;
[0005] Among them, in the iron-carbon membrane filter material, the mass percentages of the components are: sponge iron powder 60-65%, activated carbon powder 14-16%, sodium silicate 2-4%, calcium chloride 2-4%, hydroxypropyl cellulose 1-2%, expanded perlite 4-6%, and catalyst 8-9%.
[0006] Optionally, the particle size of the sponge iron powder is 2-5 mm.
[0007] Optionally, the particle size of the activated carbon powder is 0.5-1 mm.
[0008] Optionally, the activated carbon powder is at least one of coal-based activated carbon powder, wood-based activated carbon powder and fruit shell activated carbon powder.
[0009] Optionally, the expanded perlite is prepared from 30 wt % of 0.1-0.3 mm continuous grade perlite and 70 wt % of 0.3-1 mm continuous grade perlite.
[0010] Optionally, the catalyst contains titanium dioxide, nano-graphite powder and aluminum oxide.
[0011] Optionally, in the catalyst, the mass ratio of the titanium dioxide, the nano-graphite powder and the aluminum oxide is 1:(1-3):(1-3).
[0012] The present invention also provides a method for preparing the iron-carbon membrane filter material as described above, comprising the following steps:
[0013] The sponge iron powder, activated carbon powder, sodium silicate, calcium chloride, hydroxypropyl cellulose, expanded perlite and catalyst are mixed in proportion to obtain a mixture;
[0014] The mixed material is pressed into a membrane, and then sintered at 1050-1100° C. for 1-2 hours to obtain an iron-carbon membrane filter material.
[0015] The present invention also proposes a sewage treatment method based on the above-mentioned iron-carbon membrane filter material, comprising the following steps:
[0016] The iron-carbon membrane filter material is immersed in a 20 wt % polytetrafluoroethylene solution and heated at 300° C. for 1 h to obtain a modified iron-carbon membrane filter material;
[0017] Then the modified iron-carbon membrane filter material is installed in a filter;
[0018] The filter is then placed in sewage for sewage treatment.
[0019] Optionally, during the sewage treatment process, the sewage is aerated according to the filtering effect of the filter.
[0020] In the technical solution of the present invention, by selecting sponge iron powder as the iron source, selecting activated carbon powder as the carbon source, and expanding perlite as the pore-forming agent, the sponge iron powder is a porous iron powder with a high porosity, the activated carbon powder also has a developed pore structure, and the expanded perlite has a good expansion performance to increase the pores of the iron-carbon film, so that the porosity of the iron-carbon film filter material can be increased, which is beneficial to improving the sewage treatment effect. In addition, the sponge iron powder has a large specific surface area, which can provide more active surfaces, which is beneficial to improving the adsorption effect of the iron-carbon film filter material and further improving its sewage treatment effect. In addition, the combination of sodium silicate, calcium chloride, and hydroxypropyl cellulose constitutes an adhesive, which can ensure the bonding strength of the iron source and the carbon source, and the prepared iron-carbon film filter material is not easy to hydrolyze, which further improves its sewage treatment effect. At the same time, the ratio of each component is reasonable, which can ensure the synergistic effect between the components and further improve the sewage treatment effect of the iron-carbon film filter material. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0022] Figure 1 A schematic flow chart of the method for preparing the iron-carbon membrane filter material proposed in the present invention;
[0023] Figure 2 This is a schematic diagram of the process of the sewage treatment method proposed in the present invention.
[0024] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0025] To make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them.
[0026] It should be noted that, in the embodiments, those without specifying specific conditions are carried out according to normal conditions or conditions recommended by the manufacturer. Those without specifying the manufacturer of reagents or instruments used are conventional products that can be purchased commercially. In addition, the meaning of "and / or" appearing in the full text includes three parallel schemes, and "A and / or B" is taken as an example, including schemes A, B, or A and B that meet the same time. In addition, the technical schemes between the various embodiments can be combined with each other, but must be based on the ability of ordinary technicians in the field to achieve. When the combination of the technical schemes is contradictory or cannot be achieved, it should be considered that the combination of such technical schemes does not exist, and is not within the scope of protection required by the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work, all belong to the scope of protection of the present invention.
[0027] Iron-carbon membrane is a thin film material composed of iron and carbon. It is widely used in sewage treatment because of its high porosity and can effectively remove organic pollutants and suspended solids in sewage. However, the current iron-carbon membrane filter material usually has a poor porosity, which affects the sewage treatment effect.
[0028] In view of this, the present invention proposes an iron-carbon membrane filter material, comprising the following components: sponge iron powder, activated carbon powder, sodium silicate, calcium chloride, hydroxypropyl cellulose, expanded perlite and a catalyst; wherein, in the iron-carbon membrane filter material, the mass percentage of each component is: sponge iron powder 60-65%, activated carbon powder 14-16%, sodium silicate 2-4%, calcium chloride 2-4%, hydroxypropyl cellulose 1-2%, expanded perlite 4-6%, and catalyst 8-9%.
[0029] Among them, sponge iron powder can be used as an iron source to provide iron atoms for the iron-carbon membrane; activated carbon powder can be used as a carbon source to provide carbon atoms for the iron-carbon membrane, so that the sponge iron powder can form an iron-carbon alloy with the activated carbon powder to form a microporous structure for filtering sewage. Sodium silicate, calcium chloride, and hydroxypropyl cellulose are used as adhesives to bond the sponge iron powder and activated carbon powder to ensure the formation and stability of the iron-carbon membrane. Expanded perlite has good expansion properties, thereby increasing the porosity of the iron-carbon membrane, so as to be used as a pore former in the component. The catalyst can increase the active sites of the iron-carbon membrane to improve the adsorption performance of the iron-carbon membrane.
[0030] In the technical solution of the present invention, by selecting sponge iron powder as the iron source, selecting activated carbon powder as the carbon source, and expanding perlite as the pore-forming agent, the sponge iron powder is a porous iron powder with a high porosity, the activated carbon powder also has a developed pore structure, and the expanded perlite has a good expansion performance to increase the pores of the iron-carbon film, so that the porosity of the iron-carbon film filter material can be increased, which is beneficial to improving the sewage treatment effect. In addition, the sponge iron powder has a large specific surface area, which can provide more active surfaces, which is beneficial to improving the adsorption effect of the iron-carbon film filter material and further improving its sewage treatment effect. In addition, the combination of sodium silicate, calcium chloride, and hydroxypropyl cellulose constitutes an adhesive, which can ensure the bonding strength of the iron source and the carbon source, and the prepared iron-carbon film filter material is not easy to hydrolyze, which further improves its sewage treatment effect. At the same time, the ratio of each component is reasonable, which can ensure the synergistic effect between the components and further improve the sewage treatment effect of the iron-carbon film filter material.
[0031] Furthermore, the particle size of the sponge iron powder is 2-5 mm. This particle size range has a higher porosity and specific surface area, which can further improve the sewage treatment effect of the iron-carbon membrane filter material.
[0032] Furthermore, the particle size of the activated carbon powder is 0.5-1 mm. This small particle size range makes the particles of the activated carbon powder smaller, which is beneficial to increase the specific surface area and improve the filtering performance of the iron-carbon membrane filter material.
[0033] Furthermore, the activated carbon powder is at least one of coal-based activated carbon powder, wood-based activated carbon powder and fruit shell activated carbon powder. That is, the activated carbon powder can be selected from one, two or three of coal-based activated carbon powder, wood-based activated carbon powder and fruit shell activated carbon powder. The above three activated carbon powders are widely available, which is conducive to reducing the cost of iron-carbon membrane filter materials.
[0034] Furthermore, the expanded perlite is prepared by 30wt% of 0.1-0.3mm continuous grade perlite and 70wt% of 0.3-1mm continuous grade perlite. In this way, perlite with different particle sizes has different expansion properties and forms different pores, so that the pore size distribution in the iron-carbon membrane filter material can be optimized, thereby improving the filtration effect on sewage.
[0035] Furthermore, the catalyst contains titanium dioxide, nanographite powder and aluminum oxide. This arrangement can increase the active sites of the iron-carbon membrane filter material and ensure the uniformity of the active sites, thereby improving the sewage treatment performance of the iron-carbon membrane filter material.
[0036] Furthermore, in the catalyst, the mass ratio of the titanium dioxide, the nano-graphite powder and the aluminum oxide is 1:(1-3):(1-3). It should be noted that the present invention does not limit the specific mass ratio of titanium dioxide, nano-graphite powder and aluminum oxide. For example, the mass ratio of titanium dioxide, nano-graphite powder and aluminum oxide is 1:1:1. For another example, the mass ratio of titanium dioxide, nano-graphite powder and aluminum oxide is 1:3:3.
[0037] The present invention also provides a method for preparing the iron-carbon membrane filter material as described above, please refer to Figure 1 , including the following steps:
[0038] Step S11: mixing sponge iron powder, activated carbon powder, sodium silicate, calcium chloride, hydroxypropyl cellulose, expanded perlite and a catalyst in proportion to obtain a mixture;
[0039] Step S12: Pressing the mixture into a membrane, and then sintering it at 1050-1100° C. for 1-2 hours to obtain an iron-carbon membrane filter material.
[0040] In the preparation method proposed by the present invention, sponge iron powder, activated carbon powder, sodium silicate, calcium chloride, hydroxypropyl cellulose, expanded perlite and a catalyst are first mixed in proportion, then the mixture is pressed into a film, and then sintered at 1050-1100°C for 1-2 hours to obtain the desired iron-carbon membrane filter material. The preparation method has simple steps and high preparation efficiency; in addition, the preparation method proposed by the present invention is used to prepare the above-mentioned iron-carbon membrane filter material, so it has all the beneficial effects of the above-mentioned iron-carbon membrane filter material, which will not be repeated here.
[0041] The present invention also proposes a sewage treatment method based on the above-mentioned iron-carbon membrane filter material, please refer to Figure 2 , including the following steps:
[0042] Step S21: immersing the iron-carbon membrane filter material in a 20 wt % polytetrafluoroethylene solution, and heating at 300° C. for 1 h to obtain a modified iron-carbon membrane filter material.
[0043] Step S22: Then install the modified iron-carbon membrane filter material in a filter.
[0044] Step S23: placing the filter in sewage to treat the sewage.
[0045] In the treatment method proposed by the present invention, by soaking the iron-carbon membrane filter material in a polytetrafluoroethylene solution, the iron-carbon membrane filter material can be modified to have higher hydrophobicity, and water is not easily adsorbed in the pores of the iron-carbon membrane filter material, thereby improving the filtering effect on sewage.
[0046] Furthermore, during the sewage treatment process, the sewage is aerated according to the filtering effect of the filter. The iron-carbon membrane filter material consumes oxygen in the sewage when filtering the sewage. By regularly monitoring whether the filtering effect is stable, the sewage can be aerated when the filtering effect deteriorates to increase the oxygen therein and ensure the sewage treatment efficiency.
[0047] The technical solution of the present invention is further described in detail below in conjunction with specific examples and test data. It should be understood that the following examples are only used to explain the present invention and are not intended to limit the present invention.
[0048] Example 1
[0049] (1) 65 wt% of sponge iron powder, 15 wt% of activated carbon powder, 2 wt% of sodium silicate, 2 wt% of calcium chloride, 1.5 wt% of hydroxypropyl cellulose, 6 wt% of expanded perlite (prepared from 30 wt% of 0.1-0.3 mm continuous grade perlite and 70 wt% of 0.3-1 mm continuous grade perlite) and 8.5 wt% of a catalyst are mixed to obtain a mixture.
[0050] (2) The mixture is pressed into a membrane and then sintered at 1050°C for 2 hours to obtain an iron-carbon membrane filter material.
[0051] (3) immersing the iron-carbon membrane filter material in a 20 wt % polytetrafluoroethylene solution and heating it at 300° C. for 1 h to obtain a modified iron-carbon membrane filter material;
[0052] (4) then installing the modified iron-carbon membrane filter material in the filter;
[0053] (5) The filter is then placed in sewage for sewage treatment.
[0054] Example 2
[0055] (1) 60 wt% of sponge iron powder, 15 wt% of activated carbon powder, 4 wt% of sodium silicate, 4 wt% of calcium chloride, 2 wt% of hydroxypropyl cellulose, 6 wt% of expanded perlite (100 wt% of 0.1-0.3 mm continuous grade perlite) and 9 wt% of a catalyst are mixed to obtain a mixture.
[0056] (2) The mixture is pressed into a membrane and then sintered at 1100°C for 2 hours to obtain an iron-carbon membrane filter material.
[0057] (3) immersing the iron-carbon membrane filter material in a 20 wt % polytetrafluoroethylene solution and heating it at 300° C. for 1 h to obtain a modified iron-carbon membrane filter material;
[0058] (4) then installing the modified iron-carbon membrane filter material in the filter;
[0059] (5) The filter is then placed in sewage for sewage treatment.
[0060] Example 3
[0061] (1) 65 wt% of sponge iron powder, 16 wt% of activated carbon powder, 4 wt% of sodium silicate, 2 wt% of calcium chloride, 1 wt% of hydroxypropyl cellulose, 4 wt% of expanded perlite (100 wt% of 0.1-0.3 mm continuous grade perlite) and 8 wt% of a catalyst are mixed to obtain a mixture.
[0062] (2) The mixture is pressed into a membrane and then sintered at 1050° C. for 1 h to obtain an iron-carbon membrane filter material.
[0063] (3) immersing the iron-carbon membrane filter material in a 20 wt % polytetrafluoroethylene solution and heating it at 300° C. for 1 h to obtain a modified iron-carbon membrane filter material;
[0064] (4) then installing the modified iron-carbon membrane filter material in the filter;
[0065] (5) The filter is then placed in sewage for sewage treatment.
[0066] Example 4
[0067] (1) 65 wt% of sponge iron powder, 16 wt% of activated carbon powder, 2 wt% of sodium silicate, 4 wt% of calcium chloride, 1 wt% of hydroxypropyl cellulose, 4 wt% of expanded perlite (100 wt% of 0.1-0.3 mm continuous grade perlite) and 8 wt% of a catalyst are mixed to obtain a mixture.
[0068] (2) The mixture is pressed into a membrane and then sintered at 1050° C. for 1 h to obtain an iron-carbon membrane filter material.
[0069] (3) immersing the iron-carbon membrane filter material in a 20 wt % polytetrafluoroethylene solution and heating it at 300° C. for 1 h to obtain a modified iron-carbon membrane filter material;
[0070] (4) then installing the modified iron-carbon membrane filter material in the filter;
[0071] (5) The filter is then placed in sewage for sewage treatment.
[0072] Example 5
[0073] (1) 64 wt% of sponge iron powder, 14 wt% of activated carbon powder, 3 wt% of sodium silicate, 3 wt% of calcium chloride, 2 wt% of hydroxypropyl cellulose, 5 wt% of expanded perlite (100 wt% of 0.1-0.3 mm continuous grade perlite) and 9 wt% of a catalyst are mixed to obtain a mixture.
[0074] (2) The mixture is pressed into a membrane and then sintered at 1100°C for 1 hour to obtain an iron-carbon membrane filter material.
[0075] (3) immersing the iron-carbon membrane filter material in a 20 wt % polytetrafluoroethylene solution and heating it at 300° C. for 1 h to obtain a modified iron-carbon membrane filter material;
[0076] (4) then installing the modified iron-carbon membrane filter material in the filter;
[0077] (5) The filter is then placed in sewage for sewage treatment.
[0078] Comparative Example 1
[0079] (1) 65 wt% of sponge iron powder, 15 wt% of activated carbon powder, 2 wt% of sodium silicate, 2 wt% of calcium chloride, 1.5 wt% of hydroxypropyl cellulose, 6 wt% of expanded perlite (100 wt% of 0.1-0.3 mm continuous grade perlite) and 8.5 wt% of a catalyst are mixed to obtain a mixture.
[0080] (2) The mixture is pressed into a membrane and then sintered at 1050°C for 2 hours to obtain an iron-carbon membrane filter material.
[0081] (3) immersing the iron-carbon membrane filter material in a 20 wt % polytetrafluoroethylene solution and heating it at 300° C. for 1 h to obtain a modified iron-carbon membrane filter material;
[0082] (4) then installing the modified iron-carbon membrane filter material in the filter;
[0083] (5) The filter is then placed in sewage for sewage treatment.
[0084] Comparative Example 2
[0085] (1) 65 wt% of sponge iron powder, 15 wt% of activated carbon powder, 2 wt% of sodium silicate, 2 wt% of calcium chloride, 1.5 wt% of hydroxypropyl cellulose, 6 wt% of expanded perlite (100 wt% of 0.3-1 mm continuous grade perlite) and 8.5 wt% of a catalyst are mixed to obtain a mixture.
[0086] (2) The mixture is pressed into a membrane and then sintered at 1050°C for 2 hours to obtain an iron-carbon membrane filter material.
[0087] (3) immersing the iron-carbon membrane filter material in a 20 wt % polytetrafluoroethylene solution and heating it at 300° C. for 1 h to obtain a modified iron-carbon membrane filter material;
[0088] (4) then installing the modified iron-carbon membrane filter material in the filter;
[0089] (5) The filter is then placed in sewage for sewage treatment.
[0090] Comparative Example 3
[0091] (1) 65 wt% of sponge iron powder, 15 wt% of activated carbon powder, 5.5 wt% of a binder (the binder is methyl cellulose), 6 wt% of expanded perlite (prepared from 30 wt% of 0.1-0.3 mm continuous grade perlite and 70 wt% of 0.3-1 mm continuous grade perlite) and 8.5 wt% of a catalyst are mixed to obtain a mixture.
[0092] (2) The mixture is pressed into a membrane and then sintered at 1050°C for 2 hours to obtain an iron-carbon membrane filter material.
[0093] (3) immersing the iron-carbon membrane filter material in a 20 wt % polytetrafluoroethylene solution and heating it at 300° C. for 1 h to obtain a modified iron-carbon membrane filter material;
[0094] (4) then installing the modified iron-carbon membrane filter material in the filter;
[0095] (5) The filter is then placed in sewage for sewage treatment.
[0096] The porosity of the iron-carbon membrane filter materials of Examples 1-5 and Comparative Examples 1-3 was measured by a pore size analyzer, and the results are shown in Table 1. The COD value of the supernatant of the sewage after 24 hours of sewage treatment in Examples 1-5 and Comparative Examples 1-3 was measured, and the results are shown in Table 1.
[0097] Table 2 Determination of relevant properties of Examples 1-5 and Comparative Examples 1-4
[0098] Porosity (%) COD value (mg / L) Example 1 83.2 425 Example 2 81.2 430 Example 3 82.0 460 Example 4 81.5 445 Example 5 83.0 458 Comparative Example 1 75.0 635 Comparative Example 2 74.2 650 Comparative Example 3 73.5 620
[0099] As can be seen from Table 1, the porosity of the iron-carbon membrane filter material of Comparative Examples 1-3 is about 70-75%, and the COD value of the treated sewage is 600-650 mg / L, while the porosity of the iron-carbon membrane filter material of Examples 1-5 is about 80-85%, and the COD value of the treated sewage is 400-500 mg / L. Compared with Comparative Examples 1-3, the porosity of Examples 1-5 is larger, and the COD value of the treated sewage is lower, which proves that the iron-carbon membrane filter material provided by the present invention can improve the sewage treatment effect.
[0100] The above are only preferred embodiments of the present invention, and do not limit the patent scope of the present invention. For those skilled in the art, the present invention may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the patent protection scope of the present invention.
Claims
1. An iron-carbon membrane filter material, characterized in that: The components include: sponge iron powder, activated carbon powder, sodium silicate, calcium chloride, hydroxypropyl cellulose, expanded perlite and catalyst; Among them, in the iron-carbon membrane filter material, the mass percentages of the components are: sponge iron powder 60-65%, activated carbon powder 14-16%, sodium silicate 2-4%, calcium chloride 2-4%, hydroxypropyl cellulose 1-2%, expanded perlite 4-6%, and catalyst 8-9%.
2. The iron-carbon membrane filter material according to claim 1, characterized in that: The particle size of the sponge iron powder is 2-5 mm.
3. The iron-carbon membrane filter material according to claim 1, characterized in that: The particle size of the activated carbon powder is 0.5-1 mm.
4. The iron-carbon membrane filter material according to claim 1, characterized in that: The activated carbon powder is at least one of coal-based activated carbon powder, wood-based activated carbon powder and fruit shell-based activated carbon powder.
5. The iron-carbon membrane filter material according to claim 1, characterized in that: The expanded perlite is prepared from 30 wt % of 0.1-0.3 mm continuous grade perlite and 70 wt % of 0.3-1 mm continuous grade perlite.
6. The iron-carbon membrane filter material according to claim 1, characterized in that: The catalyst comprises titanium dioxide, nano graphite powder and aluminum oxide.
7. The iron-carbon membrane filter material according to claim 6, characterized in that: In the catalyst, the mass ratio of the titanium dioxide, the nano-graphite powder and the aluminum oxide is 1:(1-3):(1-3).
8. A method for preparing the iron-carbon membrane filter material according to any one of claims 1 to 7, characterized in that: The following steps are involved: The sponge iron powder, activated carbon powder, sodium silicate, calcium chloride, hydroxypropyl cellulose, expanded perlite and catalyst are mixed in proportion to obtain a mixture; The mixed material is pressed into a membrane, and then sintered at 1050-1100° C. for 1-2 hours to obtain an iron-carbon membrane filter material.
9. A sewage treatment method based on the iron-carbon membrane filter material according to any one of claims 1 to 7, characterized in that: The following steps are involved: The iron-carbon membrane filter material is immersed in a 20 wt % polytetrafluoroethylene solution and heated at 300° C. for 1 h to obtain a modified iron-carbon membrane filter material; Then the modified iron-carbon membrane filter material is installed in a filter; The filter is then placed in sewage for sewage treatment.
10. The sewage treatment method according to claim 9, characterized in that: During the sewage treatment process, the sewage is aerated according to the filtering effect of the filter.